GUAM AND THE PRC - JINGUO, Wang; ZHIZUN, Wang (CENTRAL ASIA AND THE CAUCASUS, 2008)
The GUAM organization was officially founded as a political, economic, and strategic union called upon to strengthen the sovereignty of four former Soviet republics— Georgia, Ukraine, Azerbaijan, and Moldova. In the ten years of its existence, GUAM has become an important structure striving to consolidate regional economic cooperation by developing the Europe-Caucasus-Asia transportation corridor. GUAM has also been a forum for discussing security problems, helping to settle conflicts, and eliminating other risks and threats. In 1996, Georgia, Ukraine, Azerbaijan, and Moldova made a joint statement in Vienna declaring their intention to create a union of these four countries. In April 1999, Uzbekistan joined it and the organization was named GUUAM (the abbreviation is made up of the first letters of the states involved). At that time, it was still an unofficial structure. In June 2001, the GUUAM countries held a summit in Yalta (Ukraine) and signed the Yalta Charter in which the Organization’s acting mechanism was set forth. Since then GUUAM has officially acquired the status of a regional formation.Today, GUAM is attracting the attention of the world community. Despite the fact that its foreign policy has still not found any clear balance between the “toward the West” and “away from Russia” trends, the structure’s actions are nevertheless trying to find this balance. Whatever the case, the GUAM organization appears to be a product of the fall and rise of two major geopolitical forces (the Russian geopolitical force and the Western geopolitical force led by the U.S.), as well as a result of the four states’ desire to represent a new geopolitical actor in the region. As GUAM develops, these two main geopolitical forces will continue to play a key and important role. Uzbekistan’s membership in GUAM followed by its withdrawal from it indicate the unstable position of the two leading geopolitical forces and the difficulties of turning the Organization into an effective regional geopolitical force.Despite the fact that GUAM and the People’s Republic of China do not have direct ties, during the ten years of the member states’ independence, significant progress has been seen in the interrelations between them and the PRC. As we know, the GUAM states are located on the arc that passes from China to Europe through Central Asia. They are a bridge across which Chinese goods are exported to Europe, a potential transportation corridor for Eurasian electric power, and a channel of cultural exchange between the East and the West. Consequently, as the PRC’s economy continues to develop and the policy of openness becomes more entrenched, the republic will inevitably have to activate its bilateral and multilateral contacts with the GUAM member states individually and with the Organization as a whole. So an analysis of the geopolitical reasons for the formation and actions of GUAM, its development prospects, China’s relations with this young structure, and the potential influence of the latter on the PRC’s regional policy is of immense interest.